Peristaltic Pumping System for Metering Aqueous Fertilizer - Dey, A K; Mani, Indra; Panwar, J S (Journal of Agricultural Engineering, 2006)
In dryland areas, an aqueous fertilizer seed drill helps in proper germination of seed and good establishment of crops by providing soil moisture during sowing time. Until now a suitable pumping unit to meter and disperse aqueous fertilizer is not available. The objective of the present work is to optimize the design values of the pump variables for different discharge rates suitable for different dryland winter crops. A prototype pump was developed and evaluated with two levels of reel diameter (0.30 and 0.16 m); four levels of roller spacing (15.7,8.4 ; 6.29, 11.8 cm); three levels of liquid head (0.51, 0.46, and 0.41 m); three levels ofrpm (50, 100, and 150); and three flexible tube diameters (12.7,9.6, and 6.4 mm). Discharge data was collected from the flexible tubes mounted on the rollers of the pump at a particular rpm and for the given levels of other pump variables. At 150 rpm, an individual tube of 12.7 mm diameter gave highest discharge of 4411/h. For 0.1 m variation of head, discharge varied by a maximum of 501/h. An increase of 3.9 cm roller spacing affected the discharge by a maximum of 160 I/h at 150 rpm. The developed pumping system with nine rows is capable of delivering a discharge range of 212 I/h to 3969 I/h, which satisfies the water requirement of many dryland winter crops.